An Update on National Consensus Practice Guidelines for the Treatment of Hepatitis C & Literature Review in Epidemiology of Hepatitis C in Pakistan - 2022 - Syed, Sibt ul Hasnain; Umar, Muhammad; Khaar, Hamama tul Bushra; Akhter, Tayyab Saeed; Hussain, Tassawar; Salamat, Amjad; Ahmad, Syed Irfan; Asghar, Rai Muhammad; Khurram, Muhammad; Khan, Anwar A.; Fazl-e-Hadi,; Mohsin, Aftab; et al. (Journal of Rawalpindi Medical College, 2024)
Hepatitis C is a global health problem affecting around 58 million people worldwide and killing almost 0.29 million in on one year [1]. The world has united to fight against this lethal disease in 2016 with a moto to eliminate hepatitis by 2030. To achieve this goal WHO’s World Health Assembly has set some targets and individual countries have developed their own strategies to achieve those targets [2]. Pakistan has the 2nd highest prevalence of hepatitis C in the world with 5.8% viremia positive patients [3]. Pakistan is amongst the few countries that have been assisted by the Center for Disease Control and Prevention(CDC) to prevent and control Hepatitis[4]. With the availability of Direct Acting Antivirals(DAAs), the whole paradigm of treatment of hepatitis C has changed not only globally but also in Pakistan. However, the patients in Pakistan are unable to gain access to the latest DAAs at the pace, as they are available globally. International guidelines are being updated on regular basis as per global evidence, recommending such combinations which are not readily available to many parts of the world. Hence there is a dire need to develop national guidelines, keeping in consideration the efficacy of the drugs as well as their availability, in the broader canvas of achieving the targets of eliminating Hepatitis set by WHO. In this context, our consensus guidelines are an effort to fill the gap created because of upgraded scientific evidence and possible combinations available in our part of the world. Furthermore, quite some good research and evidence has also been shared in the literature from Pakistan during last five years (2016-2021). Hence a literature review has also been carried out to update our own epidemiologic data, risk factors and treatment responses to Hepatitis C in Pakistan.